The Role and Existence of Jurisprudency in The Legal System in Indonesia - Junaedi; Jaya Mulya (Ridwan Institute, 2023)
Understanding the importance of jurisprudence in relation to the role of judges in processing a case in court, all of this indicates that jurisprudence is an integral part when judges process a case to make a decision when the written legal rules are not textually stated. And this is also the principle of freedom of action for judges, when the legal text does not stipulate concretely, this is all done to fill the legal void. However, what needs to be considered is the principle of freedom of action (freies ermeseen/discretion) for a state official (judge), may not act as freely as one's own will, but that freedom of action must result in legal decisions that are guided by the values ??of justice, the value of usefulness and the value of justice. certainty to be felt by all components of society. Thus, the role and existence of a prudential jurist in the legal system in Indonesia is highly expected to build and enforce socially just laws for all Indonesian people. For this reason, a legal issue arises, what is the role and existence of jurisprudence in the legal system in Indonesia? This requires a legal reasoning that is firm, clear and concrete so that in practice the law can be touched by all levels of Indonesian society.